Scheduling of lifting vehicle and quay crane in automated port container terminals. (1st January 2012) - Minh, Le Hoai; Yassine, Adnan; Riadh, Moussi
Container terminals are continuously facing the challenge of strong competition between ports. In this study, we present the terminal of Normandy-Le Havre port. We consider a mixed integer programming problem for the problem of assigning optimal delivery tasks to lifting vehicles. There are a lot of algorithms designed for this problem such as B&B method, cutting plane, … By using an exact penalty technique we treat this problem as a DC programme in the context of continuous optimisation. Further, we combine DCA with the classical Branch and Bound method for finding global solutions.